Anti-depressant like effects of quercetin 4'-O-glucoside from Allium cepa via regulation of brain oxidative stress and monoamine levels in mice subjected to unpredictable chronic mild stress. (2nd January 2021) - Singh, Varinder; Chauhan, Gargi; Shri, Richa
ABSTRACT: Objectives: Depression is a common neuropsychiatric disorder. The available pharmacotherapy is ineffective for a substantial proportion of patients and has numerous side effects. Therefore, finding safer drugs for the management of depression is of paramount importance. The present study was aimed to identify the compound responsible for anti-depressant like effects of Allium cepa outer scale extract (ACE) and to elucidate its mechanism of action. Methods: The anti-depressant compound from ACE was separated using bioactivity guided fractionation. Furthermore, mouse model of unpredictable chronic mild stress (UCMS) induced depressive behaviour was employed to investigate the anti-depressant like activity and potential mechanism of bioactive compound using behavioural tests (forced swim test (FST), sucrose preference test (SPT), open field test (OFT)) as well as by assessing brain oxidative stress, monoamine oxidase A and serotonin levels. Results: ACE and its ethylacetate fraction (EF) showed marked anti-depressant like effects in mice in the FST model. Chromatographic and spectroscopic studies of EF lead to the isolation of quercetin and quercetin 4'-O-glucoside (QG). Of these, QG (20 mg/kg) treated animals showed activity similar to that shown by fluoxetine in mice using FST. Thus, QG was tested for anti-depressant like activity against UCMS induced depressive behaviour in mice. Treatment of UCMS- exposed mice with QG (20 mg/kg) improved UCMS induced behaviour anomalies and restored brain biochemical parameters (oxidative stress, MAO-A activity and serotonin levels). Discussion: QG is responsible for anti-depressant like effects of ACE possibly via prevention of brain oxidative stress and restoring serotonin levels by inhibiting MAO-A activity.